1994
DOI: 10.21273/hortsci.29.12.1456
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Enrichment in `Virosa' Tomato Plant: Responses to Enrichment Duration and to Temperature

Abstract: Responses of the tomato (Lycopersicon esculentum Mill. cv. Virosa) plant to elevated CO2 concentrations applied throughout the photoperiod or part of it were studied under two temperature regimes. Plants were exposed to CO2 at 340 (control), 700, and 1000 μl·liter–1. The highest concentration was applied only at 22/16C (day/night) and 700 μl·liter–1 at 22/16C and 25/16C. Transpiration rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Concentration of fruit Ca, Mg, and K was determined following the procedure of Behboudian and Lai (1994), except that the atomic absorption spectrophotometer we used was a GBC 904AA (GBC Scientific Equipment Pty, Victoria, Australia). Concentrations of sucrose, glucose, and fructose were determined using high-performance liquid chromatography following the procedure of Behboudian and Tod (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Concentration of fruit Ca, Mg, and K was determined following the procedure of Behboudian and Lai (1994), except that the atomic absorption spectrophotometer we used was a GBC 904AA (GBC Scientific Equipment Pty, Victoria, Australia). Concentrations of sucrose, glucose, and fructose were determined using high-performance liquid chromatography following the procedure of Behboudian and Tod (1995).…”
Section: Methodsmentioning
confidence: 99%
“…For example, tomato plants grown under polyethylene tunnels with elevated CO 2 concentrations show increased yields of 32% and fruit size over 7.5 cm in diameter increased from 65% to 77% (Hartz et al , 1991). Transpiration rates of tomato were lower and photosynthetic rates higher in elevated CO 2 than at the ambient CO 2 environments (Behboudian & Robert, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have focused on the impact of increasing the CO 2 concentration from an ambient level to 700-800 µmol mol −1 , and this enrichment results in an increase in the dry mass of tomato plants of 27% when grown under florescent lamps (135 PPFD, 12 h photoperiod; Wang et al, 2009). A similar impact was shown under ambient greenhouse conditions by increasing the CO 2 concentration from an ambient level to 700-800 µmol mol −1 resulting in a 16-27% increase of dry mass (Behboudian and Lai, 1994;Pan et al, 2019).…”
Section: Figure 2 | (A-i)mentioning
confidence: 70%
“…Previous research on tomato has also shown the impact of CO 2 enrichment on the dry mass (Behboudian and Lai, 1994;Fierro et al, 1994;Li et al, 2007a;Wang et al, 2009;Pan et al, 2019). For example, studies have focused on the impact of increasing the CO 2 concentration from an ambient level to 700-800 µmol mol −1 , and this enrichment results in an increase in the dry mass of tomato plants of 27% when grown under florescent lamps (135 PPFD, 12 h photoperiod; Wang et al, 2009).…”
Section: Figure 2 | (A-i)mentioning
confidence: 99%
See 1 more Smart Citation